Measurement of νμ-induced charged-current single π⁺ production on H₂O - Assylbekov, Shamil M., author; Wilson, Robert J., advisor; Toki, Walter, committee member; Harton, John, committee member; Berger, Bruce, committee member; Hulpke, Alexander, committee member (Colorado State University. Libraries, 2015)
T2K is an international collaboration that has constructed an experiment in Japan to investigate the properties of the neutrino. It consists of two near detectors, ND280 and INGRID, and a far detector - Super-Kamiokande. ND280 has multiple sub-detectors with the π⁰ detector (PØD) being of most importance to this analysis. This work describes the first measurement of neutrino cross section for charged-current single positively charged pion (CC1π⁺) interaction channel on water (H₂O) using the PØD as target and detector. The PØD detector has been taking neutrino interaction data since 2009 in configurations with and without an integrated water target. Using a statistical water-in/water-out event rate subtraction, a measurement of the νμ-induced CC1π⁺ cross section on water is reported to be ‹σ› = 1.10 x 10⁻³⁹ +0.39·10⁻³⁹/-0.36·10⁻³⁹ cm², where the result is provided in the form of a single-bin cross section integrated over the entire T2K neutrino energy range. The measurement is based on a sample of 2,703 events selected from beam runs of $2.64 x 10²⁰ protons-on-target (POT) with the PØD water-in configuration, and 2,187 events selected from $3.71 x 10²⁰ POT with the water-out configuration. The corresponding Monte Carlo simulation predicted numbers of background events to be 1,387.2 and 1,046.0 for the water-in and water-out detector configurations, respectively. The accuracy of the result is dominated by flux and cross section models uncertainties. The data favors a systematically smaller cross section when compared to the model but within the uncertainties it is consistent with the Monte Carlo simulation prediction of $1.26 x 10⁻³⁹cm². The result, its significance, and the strategy for future CC1π⁺ measurements are discussed in conclusion.
Keywords: cross-section; pion; T2K; neutrino; charged-current; production